Penicillamine as radiation protector against gamma radiation effect on complete blood count parameters of guinea pigs - Yasser M.M El-Dessouky; Mohamed M El-Dessouky; Omnya A El-Batrawy (Wolters Kluwer Medknow Publications, 2019)
Background and aim The increasing use of nuclear technology has increased the risk of exposure to radiation. Exposure to radiation induces harms to human beings. The blood and blood-forming organs are one of the most sensitive to radiation. People exposed to high radiation doses had blood count changes, and death may occur owing to acute radiation syndromes. Therefore, radioprotective compounds are very important in clinical radiotherapy. The aim of this study was to examine the effect of penicillamine as a radiation protector agent against gamma radiation effects on complete blood count parameters of guinea pigs. Materials and methods Thirty healthy male guinea pigs were divided into three equal groups: treated irradiated (n=10), irradiated (n=10), and control (n=10) groups. The treated irradiated and irradiated groups were exposed to acute gamma radiation dose (9 kGy). The treated irradiated group received penicillamine (10 mg/kg) 1 h before exposure to radiation. Blood samples were collected soon after radiation and immediately placed in tubes containing EDTA, and these samples were used in the assessment of blood profile. Results Treated irradiated guinea pigs had significant higher red blood cell count, white blood cell count, hemoglobin concentration, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration (P≤0.05). The treated irradiated guinea pigs had significant lower relative distribution width of red blood cells by volume coefficient of variation (%) and platelet count (P≤0.05). Relative width of the distribution of platelets in volume index of the heterogeneity of platelets (%) had no significant difference between the two groups (P>0.05). Conclusion Administration of penicillamine reduced radiation damage to red blood cell count, white blood cell count, hemoglobin concentration, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration.